The Principle of the Authority of the Will in Nationality Matters: A Comparative Study in Iraqi and U.S Legislations - Tholfikar Kadhim Mutair Alakeili (International Journal of Law Research and Studies, 2025)
The principle of the sovereignty of will is considered one of the most important legal concepts, as it fundamentally influences individual interactions. Issues of nationality are closely tied to these interactions, if not the most significant among them. Delving into the concept of will in nationality leads us to explore the legal nature of nationality, which has long been a subject of debate. Some legal scholars view it as a regulatory relationship, while others see it as a contractual one. It can also be described as a mixed relationship, combining both contractual and regulatory elements. The will manifests in specific forms in matters of nationality, particularly in cases of acquisition, loss, and recovery of nationality for individuals. However, this will cannot produce any effect unless it is paired with the will of the state, represented by the competent minister, as stipulated by relevant legislation (specifically, Iraqi and US laws). Moreover, nationality serves many functions, most notably the investment function, which has become a fundamental part of the economies of some countries and is closely tied to the concept of will. At the same time, judicial oversight remains essential in addressing issues of nationality, ensuring a balance between the interests of individuals and the state.